The administration of intermittent parathyroid hormone affects functional recovery from pertrochanteric fractured neck of femur: a protocol for a prospective mixed method pilot study with randomisation of treatment allocation and blinded assessment (FRACTT). Issue 1 (29th January 2014) - Chesser, Tim; Fox, Rebecca; Harding, Karen; Greenwood, Rosemary; Javaid, Kassim; Barnfield, Steven; Halliday, Ruth; Willett, Keith; Lamb, Sallie
Abstract : Introduction: Pertrochanteric hip fractures occur in an elderly population and cause considerable morbidity and loss of functional ability as the fracture heals. Recently, parathyroid hormone (PTH), which is licensed for the treatment of osteoporosis, has been shown to potentially accelerate bone healing in animal and human studies. If its administration could allow a faster functional recovery after pertrochanteric hip fracture, then a patient's hospital stay may be reduced and rehabilitation could be potentially accelerated. PTH can currently only be administered by subcutaneous injection. The acceptability of this intervention is unknown in this elderly population. The aim of this pilot study is to inform the design of a future powered study comparing the functional recovery after pertrochanteric hip fracture in patients undergoing standard care versus those who undergo administration of subcutaneous injection of PTH. Methods and analysis: The study is an open label, prospective, randomised, comparative pilot study with blinded outcomes assessment to establish feasibility of the trial design. Patients will be randomised to receive a 6-week course of PTH or usual treatment. Functional outcomes will be assessed at 6 weeks and 12 weeks. Blinded assessment will be used to minimise the effect of bias of an open label study design. A nested qualitative study will investigate the patient experience of, and expectations following, hip fracture and the patient important aspects of recovery compared with the outcome measures proposed. Results: Results will be analysed to establish the potential recruitment, compliance and retention rates using 95% CIs, and trial outcomes quoted with SDs and 95% CIs for the effect size. Ethics and dissemination: The study has been approved by the South West 2 Research Ethics committee (reference 10/H0206/34). The findings of this study will be disseminated to the medical community via presentations to orthopaedic, orthogeriatric and osteoporosis societies, and their relevant specialist journals. Trial Registration: ISRCTN Register reference number: ISRCTN03362357 . Eudract Number: 2010-020081-22